Study of Separator Damage Effects on Lithium Ion Battery Cell's Performance - (:unkn) unknown (My University, 2018)
In the world of energy storage technology, Lithium Ion batteries are considered to be among the most efficient in terms of energy- and power density. However, many consumers are fearful of the potential dangers involved in using this technology. One approach to improving the battery’s safety is to focus on design of the cell itself. The separator seems to be the obvious choice in a quest to improve its safety since alterations to the other components of a battery could easily compromise the efficiency of the cell. The methods herein provide experimental results and insights that could be used to optimize the safety and efficiency of the battery’s separator under various damage conditions.
Keywords: Battery Separators; Lithium-Ion; Lithium Ion Separators